Systematic Hydrogen‐Bond Manipulations To Establish Polysaccharide Structure–Property Correlations. Issue 37 (19th August 2019) - Yu, Yang; Tyrikos‐Ergas, Theodore; Zhu, Yuntao; Fittolani, Giulio; Bordoni, Vittorio; Singhal, Ankush; Fair, Richard J.; Grafmüller, Andrea; Seeberger, Peter H.; Delbianco, Martina
Abstract: A dense hydrogen‐bond network is responsible for the mechanical and structural properties of polysaccharides. Random derivatization alters the properties of the bulk material by disrupting the hydrogen bonds, but obstructs detailed structure–function correlations. We have prepared well‐defined unnatural oligosaccharides including methylated, deoxygenated, deoxyfluorinated, as well as carboxymethylated cellulose and chitin analogues with full control over the degree and pattern of substitution. Molecular dynamics simulations and crystallographic analysis show how distinct hydrogen‐bond modifications drastically affect the solubility, aggregation behavior, and crystallinity of carbohydrate materials. This systematic approach to establishing detailed structure–property correlations will guide the synthesis of novel, tailor‐made carbohydrate materials. Abstract : Calling the tune : Tailor‐made cellulose oligosaccharide analogues, including methylated, deoxygenated, deoxyfluorinated, and carboxymethylated cellulose, were prepared by sequential addition of monomeric building blocks using automated glycan assembly. Seven different building blocks bearing modifications to disrupt specific hydrogen bonds enabled the three‐dimensional shapes and properties of the materials to be tuned.